How Synonymic Taste Words Alter Perceived Taste in American Consumers - Tamara Marie Johnson; Simone Eveline Pfenninger (Languages)
Investigations into crispy and crunchy in American English have demonstrated that these synonymic taste words have differing effects on perceived taste depending on association. To test the generalizability of these findings, category fluency tasks were used to elicit foods and beverages more and less associated with several pairs of synonymic taste words. Next, taste tests were conducted using synonymic taste words and some of their more and less associated products as stimuli. The results showed that more associated taste words have a marginally significant, positive effect on taste ratings, with significant interaction effects for certain products resulting in lower taste ratings. This study confirms that synonymic taste words beyond crispy and crunchy can alter perceived taste in American consumers. Moreover, it demonstrates that the underlying mechanisms are complex and, in addition to association, depend on the particular food or beverage as well as further factors.